Ethnography and Evaluation: Their Relationship and Three Anthropological Models of Evaluation - Youker, Brandon W. (Journal of MultiDisciplinary Evaluation, 2005)
This paper examines the relationship between ethnographic research methods and evaluation theory and methodology. It is divided into two main sections: (a) ethnography in evaluation and (b) anthropological models of evaluation. Three levels of the leading anthropological models of evaluation are summarized, which include responsive evaluation, goal-free evaluation, and constructivist evaluation. In conclusion, (a) there is no consensual definition of ethnography; (b) in many circumstances, ethnographic evaluation models may be beneficial; and (c) ethnography can be used in evaluation but requires a high level of analysis to transform ethnographic data into useful information for eliciting an evaluative conclusion.